2023
DOI: 10.14238/sp25.2.2023.75-9
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan dan Sikap Orang Tua Mengenai Buku Kesehatan Ibu dan Anak terhadap Perilaku Pemanfaatannya

Debora Octo Luana,
Lili Rohmawati,
Wisman Dalimunthe
et al.

Abstract: Latar belakang. Ibu dan anak merupakan kelompok rentan dalam keluarga dan sekitarnya sehingga perlu mendapatkan prioritas dalam penyelenggaraan pelayanan kesehatan. Buku Kesehatan Ibu dan Anak berperan sebagai alat deteksi dini gangguan kesehatan ibu dan anak, serta sebagai alat komunikasi yang memberikan informasi dan penyuluhan tentang pelayanan kesehatan ibu dan anak, termasuk rujukan dan standar pelayanan, gizi, imunisasi, dan tumbuh kembang balita kepada ibu, keluarga, dan masyarakat. Pemanfaatan buku ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Several studies have assessed the knowledge, attitudes, and utilization associated with the MCH book. Studies have indicated that the maternal knowledge of the MCH book is sufficient (59.3%) (Erawati et al, 2020) or good (57.8%) (Luana et al, 2023). However, while attitudes towards the MCH book appear to be good overall (97.8%), some studies have found the book is never (73.3%) (Luana et al, 2023) or infrequently utilized (52.6%) (Lestari et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have assessed the knowledge, attitudes, and utilization associated with the MCH book. Studies have indicated that the maternal knowledge of the MCH book is sufficient (59.3%) (Erawati et al, 2020) or good (57.8%) (Luana et al, 2023). However, while attitudes towards the MCH book appear to be good overall (97.8%), some studies have found the book is never (73.3%) (Luana et al, 2023) or infrequently utilized (52.6%) (Lestari et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that the maternal knowledge of the MCH book is sufficient (59.3%) (Erawati et al, 2020) or good (57.8%) (Luana et al, 2023). However, while attitudes towards the MCH book appear to be good overall (97.8%), some studies have found the book is never (73.3%) (Luana et al, 2023) or infrequently utilized (52.6%) (Lestari et al, 2023). Most prior research on the completeness of MCH books has assessed the maternal health section during pregnancy and the postpartum period (Amalia & Windarti, 2020;Dharmawan, 2019;Zakiah et al, 2021), with evidence of its completeness during the toddler years being scarce.…”
Section: Introductionmentioning
confidence: 99%